2012
DOI: 10.1021/cg3014305
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of LaFeO3 Nanostructure Dendrites: A Systematic Investigation of Growth Mechanism, Properties, and Biosensing for Highly Selective Determination of Neurotransmitter Compounds

Abstract: Single-crystalline novel LaFeO 3 dendritic nanostructures are synthesized by a well-controlled, surfactantassisted facile hydrothermal process. The morphology of the material is investigated by high-resolution transmission and scanning electron microscopy. The crystal nature and chemical composition of LaFeO 3 dendritic nanostructures are revealed from the X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. Structural characterizations imply the preferential growth along the [121] dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 44 publications
2
76
0
Order By: Relevance
“…The surfactant was found to have a specific mechanism involved in the synthesis of nanostructures; that is, during the synthesis process, the surfactants were absorbed by the growing crystal and depending upon the precursor concentration and surfactant property, they moderate the growth rate of crystal faces, which thereby controls the shape and size through an Ostwald ripening process. 37 It was observed that the flower and hexagonal morphologies of CuAlO 2 structures could be reproduced using the surfactant-assisted hydrothermal process used in the present study. Further, CuAlO 2 samples without surfactant were also prepared, where only agglomerated structures were observed ( Figure S1, Supporting Information), which is of no interest for the present study.…”
Section: Resultsmentioning
confidence: 52%
“…The surfactant was found to have a specific mechanism involved in the synthesis of nanostructures; that is, during the synthesis process, the surfactants were absorbed by the growing crystal and depending upon the precursor concentration and surfactant property, they moderate the growth rate of crystal faces, which thereby controls the shape and size through an Ostwald ripening process. 37 It was observed that the flower and hexagonal morphologies of CuAlO 2 structures could be reproduced using the surfactant-assisted hydrothermal process used in the present study. Further, CuAlO 2 samples without surfactant were also prepared, where only agglomerated structures were observed ( Figure S1, Supporting Information), which is of no interest for the present study.…”
Section: Resultsmentioning
confidence: 52%
“…All the peaks were calibrated using C1s (284.6 eV) as the reference. La peaks were observed at 845.8 eV which corresponds to spin-orbit splitting of 3d 5 A N 2 adsorption-desorption isotherm (Fig. 2(d)) of LaFeO 3 microspheres exhibit a type-IV isotherm with a hysteretic loop in the range 0.6-1.0 P/P o , indicating the presence of mesoporosity.…”
Section: Structural Thermal Composition and Surface Area Analysis Omentioning
confidence: 98%
“…Most researchers have used crystalline LaFeO 3 nanoparticles toward potential applications, but data comparison with respect to amorphous LaFeO 3 nanoparticles is limited [46,[64][65][66]. To elucidate the effects of surfactant (CTAB) and LaFeO 3 nanofillers (amorphous vs. crystalline), different fillers were added into PVA matrix (which is the major dominant constituent of the QPVA) to form composites, and their conductivities were measured at 30-60 • C. The fillers included pure CTAB, pure LaFeO 3 nanofillers (amorphous phase without CTAB), as-synthesized LaFeO 3 nanofillers (CTAB-functionalized amorphous phase), and annealed LaFeO 3 nanofillers (crystalline).…”
Section: Role Of Ctab Surfactantmentioning
confidence: 99%